Le trophée de chasse dans la littérature cynégétique, une anthropomuséologie des restes animaliers - Antoine Jeanne (Les Cahiers de l'École du Louvre)
This article intends to revisit the way the ethnologist envisaged his field from a distance. Through the study of non-scientific literature from the nineteenth to the twenty-first centuries, Antoine Jeanne delves into the works recommended by his respondents to perfect his understanding of the hunting trophy. The author thus reflects on the way in which the ethnologist mobilises narrative and fiction to explore the imaginations of contemporary hunters and to conduct anthropomuseological research of the hunting trophy.